2018
DOI: 10.4149/bll_2017_120
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of cardiac surgery‑associated acute kidney injury by microRNA-21

Abstract: We tested the hypothesis whether microRNA-21 (miR-21) can detect CSA-AKI earlier than serum creatinine (sCr). A total of 103 patients scheduled to undergo cardiac surgery. CSA-AKI was defined as sCr > 0.3 mg/dl 24 h after surgery. The patients were divided into two groups according to whether or not developing AKI after surgery. Serum and urinary miR-21 were measured prior to, and 6, 12 and 24 h after surgery. Baseline serum and urinary levels of miR-21 in AKI group were lower than in non-AKI group. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This is in keeping with other findings that urinary miR-21 appeared to be more associated with AKI prognosis than plasma miR-21 levels (39,40). Serum miR-21 levels were associated with the development of AKI when sampled before cardiac surgery (41) and 6 hours after cardiac surgery (42). In the latter study, urinary miR-21 levels were also associated with AKI (42).…”
Section: Microrna As Biomarkers Of Kidney Diseasesupporting
confidence: 90%
See 1 more Smart Citation
“…This is in keeping with other findings that urinary miR-21 appeared to be more associated with AKI prognosis than plasma miR-21 levels (39,40). Serum miR-21 levels were associated with the development of AKI when sampled before cardiac surgery (41) and 6 hours after cardiac surgery (42). In the latter study, urinary miR-21 levels were also associated with AKI (42).…”
Section: Microrna As Biomarkers Of Kidney Diseasesupporting
confidence: 90%
“…Serum miR-21 levels were associated with the development of AKI when sampled before cardiac surgery (41) and 6 hours after cardiac surgery (42). In the latter study, urinary miR-21 levels were also associated with AKI (42). Interestingly, ischemic preconditioning could increase endogenous miR-21 expression and further protect kidney function (43).…”
Section: Microrna As Biomarkers Of Kidney Diseasementioning
confidence: 87%
“…MiR-21 was up-regulated in several distinct animal models of kidney diseases as well as both human AKI and chronic kidney disease (CKD) (Loboda et al, 2016 ). Thus, miR-21 is considered a potential biomarker for cardiac surgery-associated acute kidney injury, hypertensive kidney injury and fibrosis (Gaede et al, 2016 ; Arvin et al, 2017 ; Chen et al, 2017 ). However, the effect of miR-21 on renal injury remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…One clinical study found that miR-21 levels increased both in plasma and urine with increasing AKI severity after adult cardiac surgery [ 63 ]. However, another clinical study found decreased, but not increased, expression of miR-21 in cardiac surgery-associated AKI patients [ 64 ]. Recently, a large-scale study found that urine and blood miR-21 expression in the remote ischemic preconditioning group increased significantly in children with congenital heart disease undergoing cardiopulmonary bypass surgery [ 65 ].…”
Section: Mirnas In Acute Kidney Injurymentioning
confidence: 99%